(3eLehY aj GdcjejGAs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf ChdG hGNQkG hXGgQkG hHGWfkG Efg bO SHb dfG bHd cJGHfG gPG YOI cJH ai gPg GdCUhd GdHGH GdChd ai JMOjO CUhd GdUfGYI s
(3BNQgG (B:s
(3hCgd gPG GdQCi jbhdhf Cf LejY GdYdhe dgG BNQ dfJGFLgG hgh WQjb UYH agPG LejY eG jLH Cf jbde ai gPg GdUfGYI Je GdLRA GdYTQhf hHJeGeI Je cJGH GdQjGV s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdK YTQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1422s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs